Flexural behavior of reinforced concrete beam with polypropylene under static load / Zainal Abidin Mohd. Fauzi - Mohd. Fauzi, Zainal Abidin (Faculty of Civil Engineering, 2001)
The increase in the use of the fiber reinforced concrete in modem construction is tremendously high. Thus, its behavior need to be understood clearly. In this project, the flexural behavior of reinforced concrete beam with additive of polypropylene under static load with respect to serviceability and ultimate limits were carried out. Two 'y reinforced concrete beams with a characteristic strength of 30N/mm have been casted and tested of which one of them with additive of fiber. The results reveal that there were an improvement in cracking and deflection when Polypropylene fiber added to the reinforced concrete beam besides reduced the number of cracking to the Beam. From the experimental, it showed that the modulus of elasticity for the Fiber Reinforced concrete beam was 30.4KN/mm2 while for the reinforced concrete beam without Polypropylene fiber was 20.29KN/mm . Regarding to these results, it is recommended to use the Polypropylene fiber as an additive to the concrete since it can reduce the cracking and deflection of the elements.